Orthodontically driven corticotomy : tissue engineering to enhance orthodontic and multidisciplinary treatment - Brugnami, Federico, 1967-; Caiazzo, Alfonso, 1968- (John Wiley & Sons Inc., 2015)
"The first book of its kind, Orthodontically Driven Corticotomy describes how to apply this innovative technique to orthodontic treatment protocols. More than simply discussing orthodontic applications, the editors demonstrate how corticotomies enhance inter- and multidisciplinary treatments. Different surgical approaches are described, with indications on how to select the most appropriate one, to increase efficiency of orthodontic movement, and minimize the surgical exposure for the patient at the same time. Readers learn how to apply the technique to expand the basal bone, regenerate periodontal tissues, combine corticotomy and anchorage devices, manage partial edentulism, treat impacted teeth, and become more efficient in orthodontic treatment. Surgical steps are demonstrated with more than 650 clinical photographs and 200 illustrations"--Provided by publisher.